Principles of marketing / Philip Kotler, Gary Armstrong - Kotler, PhilipAuthor
Updated and streamlined, 'Principles of Marketing', 11th edition, tells the stories that reveal the drama of modern marketing, reflecting the major trends and forces that are impacting this dynamic and ever-changing field.